DIFFERENT ASPECTS OF QUALITY OF PROFESSIONALLY ORIENTED FOREIGN LANGUAGE TEACHING - Zhurbenko, Natalia; Yarimaka, Valentina; Chalova, Olga (Revista Inclusiones, 2021)
Following the goals of sustainable development in the sphere of teaching professionally oriented foreign languages; the paper presents the results of the theoretical research aimed at understanding of different aspects of quality of professionally oriented foreign language teaching. The authors consider the concept of learning quality, assuming that the learning process is not a straightforward development of skills. To reach the objective of the research we set a number of tasks: defining properties and features of the quality of teaching and learning professionally oriented foreign languages, considering the properties of quality, aspects of quality that should be improved, determining the spheres for the following field research, describing the educational process as we see it from the point of view of improving quality. This paper attempts to explain some aspects of the modern educational process that may affect the quality of the learning system. The paper assumes that the quality of the learning process depends on a large number of external and internal factors inherent in a given society, and on the knowledge and correct use of the results of previous experience in foreign languages teaching.